Budaya Organisasi Dan Pengaruhnya Terhadap Kinerja Karyawan di Koperasi Rejo Makmur Kabupaten Semarang - Ningrum, Setya; Natoil, Natoil; Sofiana, Rina (STIE Semarang, 2024)
This research aims to determine the influence of organizational culture on employee performance, and determine the influence of leadership on employee performance at Rejo Makmur Cooperative Semarang Regency. The population in this research is all employees at Rejo Makmur Cooperative Semarang Regency has 51 employees. This research did not carry out sampling. The research method used is a descriptive analysis method, a statistical analysis method consisting of multiple linear regression analysis, partial significance testing (t-test) and testing the coefficient of determination (R2). The research results show that there is a significant positive influence between organizational culture and leadership on employee performance. The suggestion in this research is the importance of supervisors in improving organizational culture and good leadership. This is done so that employee performance can increase.